Analysis of the spatiotemporal evolution of the coastline of Jiaozhou Bay and its driving factors. (1st July 2022) - Cai, Haolin; Li, Chengming; Luan, Xueke; Ai, Bo; Yan, Luyan; Wen, Zhen
Abstract: Studying the spatiotemporal changes in coastlines and the underlying mechanisms is important for the rational development and utilization of coastal resources and sustainable economic development. For the first time, this study analyzes twenty years of spatiotemporal changes in the coastline of Jiaozhou Bay (JB), Qingdao, by integrating high-resolution remote sensing images from Google Maps and Landsat time series data at five-year intervals from 2000 to 2020. Five coastlines were extracted using the normalized difference water index and Otsu threshold segmentation method. The index of coastline type diversity (ICTD), index of coastline utilization degree (ICUD), and end point rate were applied to the systematic study of the evolution of the coastline of JB for the first time. The results show that the total length of coastline decreased, with the natural coastline accounting for only approximately 10% of the sharp decrease in the first five years and slow increase in the last 15 years. The ICTD was >0.7, and the ICUD increased from 231.7 to 261.5, indicating an increase in the influence of humans. The coastline also moved seaward with an average accretion rate of 47.5 km/year, resulting in a 24.5 km 2 reduction in the area of the bay over the 20 years. This was caused by human activities such as port construction. In addition, the degree of correlation between coastline changes and socioeconomic factors was analyzed using grey correlation analysis. Based on this, the forces driving the changes to the coastline were explored, and suggestions for coastal zone management were proposed.